Activities of the summer party of the 29th Japanese Antarctic Research Expedition in 1987-1988 - Natsuo Sato (National Institute of Polar Research, 1990)
This report outlines the summer activities of the 29th Japanese Antarctic Research Expedition (JARE-29) in 1987-1988. The icebreaker SHIRASE, carrying 52 expedition members, 5 Japanese observers and 2 Chinese scientists led by Dr. O. WATANABE with cargo of about 900 t, left Tokyo on 14 November 1987. After calling at Fremantle in Western Australia, where an American scientist joined the party, the ship arrived at Breid Bay on 17 December. The helicopter and surface transportation of 160 t of cargo from the ship to Asuka Station was completed by 30 December. Two airplanes operated at Asuka Station by JARE-28 returned to the SHIRASE on 28 December. The ship reached Syowa Station on 2 January 1988,and the transportation of 730 t of cargo by means of helicopter and surface was completed by 12 January. After the accomplishment of constructing and fieldwork in the Syowa Station area, the SHIRASE left Syowa Station on 5 February and arrived again at Breid Bay on 7 February. The field party of the Sor Rondane Mountains was collected by her. On the way from Breid Bay to Sydney, Australia, the ship stopped over at Molodezhnaya Station and Amundsen Bay for a fieldwork. On 27 March, the members of expedition came back to the Tokyo Airport via Sydney, and the ship returned to the Tokyo Port on 12 April. The following scientific activities were carried out during the summer operation of JARE-29 : a) aerial photographic survey, geological, geomorphological, and geodetic observations in the Sor Rondane Mountains region; b) geological, geomorphological, and biological surveys in the Mts. Vechernyaya and Riiser-Larsen regions; c) biological and oceanographic observations and gravity measurements in the Syowa Station area; d) seafloor geomagnetic observations in Breid Bay; e) meteorological, oceanographical and ionospheric observations and sea gravity measurements on board the SHIRASE.